2013
DOI: 10.19026/ajfst.5.3129
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Zinc on Growth and Physiological Characters of Flag Leaf and Grains of Winter Wheat after Anthesis

Abstract: The study explored the effects of supplementing 0, 200, 400 and 800 mg/kg Zn in cultivating soils on the growth and yield characters of winter wheat Zhoumai 18 and Aikang 58, the two popular wheat varieties currently in Henan, China, planted in pots in a screen house after anthesis during 2009-2010. The results indicated that the differences in activities of Peroxidase (POD), Superoxide Dismutase (SOD) and Catalase (CAT) in flag leaf and grains at 5 and 25 days after anthesis mainly came from differences in Zn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“… Kutman et al (2012) showed that the increase in the grain yield due to improved N and Zn supply was parallel to the increase in spike number and eventually grain amount. Nadim et al (2012) and Jiang et al (2013) in their respective studies pointed out higher leaf area index and photosynthetic rate in connection with soil applied Zn at sowing time. Ekiz et al (1998) noticed significant increase in wheat and other cereals grain yield when Zn (7 kg ha -1 ) was applied in Zn- deficient soil.…”
Section: Discussionmentioning
confidence: 89%
“… Kutman et al (2012) showed that the increase in the grain yield due to improved N and Zn supply was parallel to the increase in spike number and eventually grain amount. Nadim et al (2012) and Jiang et al (2013) in their respective studies pointed out higher leaf area index and photosynthetic rate in connection with soil applied Zn at sowing time. Ekiz et al (1998) noticed significant increase in wheat and other cereals grain yield when Zn (7 kg ha -1 ) was applied in Zn- deficient soil.…”
Section: Discussionmentioning
confidence: 89%
“…Therefore, its higher doses can be attributed to increased protein contents. Levels of Zn also played important role in stimulating protein contents in grains (Nadim et al, 2012;Jiang et al, 2013) Zn is indispensable nutrient for N metabolism due to its catalytic influence on numerous enzyme systems, biochemical activities responsible for nitrate reduction and protein synthesis (Khare and Dixit, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Its acute deficiency can lead up to 40% reduction in crop yield (Salvagotti and Miralles, 2007;Kutman et al, 2010;Kutman et al, 2011). Chlorophyll and auxin synthesis necessitate adequate Zn contents in plant tissues (Nadim et al, 2012;Jiang et al, 2013). Zinc also performs as cofactor to various enzymes hence, controls their activities.…”
Section: Introductionmentioning
confidence: 99%
“…SOD is the elementary scavenger enzyme involved in the detoxification of ROS in plant and converts superoxide to H 2 O 2 and O 2 (Miller et al 2007). SOD, an antioxidative enzyme, catalyzes the dismutation of free radical into H 2 O 2 and O 2 which in turn inhibits lipid peroxidation of membrane and hence may delay flag leaf senescence (Jiang et al 2013;Xu et al 2017), whereas CA is involved in photosynthesis and acts as storage pool of Zn in leaf (Han et al 2004). The enhancement in SOD and CA activities due to Zn helps in greater accumulation of photosynthates as well as Zn concentration in different plant parts (Bharti et al 2014;Singh et al 2019).…”
Section: •-mentioning
confidence: 99%